Yakunchik: Agreeing on water management after the violence - Oré Vélez, María Teresa (2006)
The Yayunkchik Platform emerged at the end of 1998, in the city of Huamanga - capital of the department of Ayaucho, in the central highlands of Peru -, when the region was going through the effects of a severe drought caused by the El Niño Phenomenon (FEN, 1998). . At the end of this year, a workshop on water management was held; a small nucleus of interested local institutions was formed in it, which would later give rise to the Platform.